Histopathological Analysis of Internal Limiting Membrane Surgically Peeled From Eyes with Epiretinal Membrane. (1st February 2016) - Beyazyildiz, Özlem; Tirhiş, Mehmet Hakan; Hekimoğlu, Emine Rümeysa; Beyazyildiz, Emrullah; Kaymaz, Figen; Yilmazbaş, Pelin; Öztürk, Faruk
ABSTRACT: Purpose : To investigate histopathological changes of internal limiting membrane (ILM) in patients with epiretinal membrane (ERM) Materials and Methods : Forty-two eyes of 42 patients who were diagnosed as ERM and enrolled for vitreoretinal surgery were included in this study. Brilliant Blue G (BBG) was used to stain the ILM in all patients. ILM was peeled in all subjects and analyzed by light microscopy (methylene blue-Azur II × 40). ILM samples were then fixed in 2.5% glutaraldehyde solution and examined in JEOL-JEM 1400 and 2100F electron microscope and photographed by CCD camera (Gatan Inc., Pleasanton, CA). Results : Remained ERM fragments were observed on 80% of ILM's. Vacuolization of ILM was observed in a patient with diabetic ERM. There were cells and cellular fragments observed mostly at retinal side of ILM which was likely to be a fragment of Muller cells of retina. Conclusions : Most of the ILM's had residual ERM tissue and contained cells and cellular fragments at retinal side of ILM's. ILM peeling might have a role in decreasing ERM recurrence by removal of residual ERM tissues.